GRAVITY MODEL IN FOREIGN TRADE (APPLICABALE CASE ABOUT THE SKINS IN IRAQ DURING THE PERIOD (1990-2014) - & AL_Badri, AL_Jubori (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The Gravity Model considered one of the important models in foreign trade, because it is used to explain the most important determinants of the state export of it’s exporting goods and determine competitive state for exports of the country in world market of its exports, besides it give an idea about most important countries in exporting export goods. The study aims to determine most important factors affecting on flow of Iraqi skins to world market, and measuring influence of these factors and determine suitable model to understand most important determinants of foreign trade of Iraqi skins with most important trading partners. The study proved that per capita of GDP, quantity of commodity produced by country, quantity of commodity exports from country to global market and export price (FOB) of commodity, were the most important determinants of flow of Iraqi skins to global market, because these factors formed about (%53) of determinants of flow of Iraqi skins to global market. By analyzing the model of most important determinants of flow of Iraqi skins with most important trading partners (Jordan and UAE), the study found that the most important determinants of flow of Iraqi skins with most important trading partners were per capita of GDP representing economic size of two partners, number of population in two partners and the distance between trading capitals of them with invers sign. These factors compatible with gravity trade model between states, and these factors determine (%89) of happening changes in flow of Iraqi skins to most important trading partners.